Performance Evaluation of Advanced PLL Techniques For Accurate FFPS Component Extraction - Saritha, M; Sidram, M H (IAES Indonesian Section, 2024)
It is very necessary to adopt fundamental frequency positive sequence (FFPS) element extraction methods in order to maximise the efficiency of integrating and handling the use of renewable energy sources (RES). The decision to act in this manner is made with the purpose of contributing to the accomplishment of the aforementioned aim. The capability of the synchronous references frame phase-locked loop to reject variations over a broad variety of grid conditions is enhanced as a result of this. This is particularly true for voltage sags and surges that are accompanied by harmonics, irrespective of whether the harmonics are the result of balanced or unbalanced electrical current fluctuations. The accuracy of the extraction of FFPS components is significantly influenced by the frequency deviation in SRF-PLL systems. The frequency deviation is another critical component. This is a result of the frequency deviation not remaining constant. An investigation is being conducted to ascertain the effectiveness of a various advanced PLL techniques, such as the cascaded delayed signal cancellation (CDSC), the dual second-order generalized integrator (DSOGI) and the multiple delayed signal cancellation (MDSC). The objective of conducting this assessment is to facilitate the evaluation of the efficacy of these strategies, which is the reason for its implementation. The CDSC and MDSC PLL have been demonstrated to be preferable to other PLLs due to their ability to distinguish between even and odd harmonics. This is due to the fact that each of these harmonics possesses its own distinctive characteristics. This may be attributable to its capacity to independently identify either harmonic. The MATLAB simulation results is provided to demonstrate the exceptional performance of these highly advanced PLLs.